Perancangan Desain UI/UX Aplikasi Somnia untuk Manajemen Pola Tidur Berbasis Mobile - Ni Putu Meita Kartika Dewi; Ida Ayu Gde Suwiprabayanti Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Sleep is an essential basic need for human health and well-being. However, in the midst of a busy modern lifestyle, achieving ideal sleep becomes a challenge due to several factors. Consequently, lack of sleep can cause a negative impact on both physical and mental health. Based on these problems, this research aims to design the sleep management application